Creation & the environment : an Anabaptist perspective on a sustainable world - Redekop, Calvin Wall, 1925- (Center books in Anabaptist studies., 2000)
Recent years have seen a shift in the belief that a religious world-view, specifically a Christian one, precludes a commitment to environmentalism. Whether as "stewards of God's creation" or champions of "environmental justice," church members have increasingly found that a strong pro-ecology stand on environmental issues is an integral component of their faith. But not all Christian denominations are latecomers to the issue of environmentalism. In Creation and the Environment Calvin W. Redekop and his co-authors explain the unique environmental position of the Anabaptists, in particular the Mennonites. After a brief survey of the major forces contributing to the word's present ecological crisis, Creation and the Environment explores the uniquely Anabaptist view of our relationship to what they see as the created order. In rural Amish and Mennonite communities, they explain, the environment - especially the "land"--Is considered part of the Kingdom God plans to establish on earth. In this view, the creation is part of the divine order, with the redemption of humankind inextricably linked to the redemption and restoration of the material world. The well-being a purpose of creation and human history are thus seen as completely interdependent. Contributors: Heather Ackley Bean, Claremont Graduate School; Kenton Brubaker, Eastern Mennonite University; Thomas Finger, Claremont Graduate School; Karen Klassen Harder, Bethel College, Kansas; James Harder, Bethel College, Kansas; Lawrence Hart, Cheyenne Cultural Center, Clinton, Oklahoma; Theodore Hiebert, McCormick Theological Seminary; Karl Keener, Pennsylvania State University; Walter Klaassen, Conrad Grebel College; David Kline, Holmes County, Ohio; Calvin W. Redekop, Conrad Grebel College; Mel Schmidt; Dorothy Jean Weaver, Eastern Mennonite University; Michael Yoder, Northwestern College, Iowa